Plasmodium vivax lineages: geographical distribution, tandem repeat polymorphism, and phylogenetic relationship (2011)
Background: Multi-drug resistance and severe/ complicated cases are the emerging phenotypes of vivax malaria, which may deteriorate current anti-malarial control measures. The emergence of these phenotypes could be associated with either of the two Plasmodium vivax lineages. The two lineages had been categorized as Old World and New World, based on geographical sub-division and genetic and phenotypical markers. This study revisited the lineage hypothesis of P. vivax by typing the distribution of lineages among global isolates and evaluated their genetic relatedness using a panel of new mini-satellite markers. Methods: 18S SSU rRNA S-type gene was amplified from 420 Plasmodium vivax field isolates collected from different geographical regions of India, Thailand and Colombia as well as four strains each of P. vivax originating from Nicaragua, Panama, Thailand (Pak Chang), and Vietnam (ONG). A mini-satellite marker panel was then developed to understand the population genetic parameters and tested on a sample subset of both lineages. Results: 18S SSU rRNA S-type gene typing revealed the distribution of both lineages (Old World and New World) in all geographical regions. However, distribution of Plasmodium vivax lineages was highly variable in every geographical region. The lack of geographical sub-division between lineages suggests that both lineages are globally distributed. Ten mini-satellites were scanned from the P. vivax genome sequence; these tandem repeats were located in eight of the chromosomes. Mini-satellites revealed substantial allelic diversity (7-21, AE = 14.6 +/- 2.0) and heterozygosity (He = 0.697-0.924, AE = 0.857 +/- 0.033) per locus. Mini-satellite comparison between the two lineages revealed high but similar pattern of genetic diversity, allele frequency, and high degree of allele sharing. A Neighbour-Joining phylogenetic tree derived from genetic distance data obtained from ten mini-satellites also placed both lineages together in every cluster. Conclusions: The global lineage distribution, lack of genetic distance, similar pattern of genetic diversity, and allele sharing strongly suggested that both lineages are a single species and thus new emerging phenotypes associated with vivax malaria could not be clearly classified as belonging to a particular lineage on basis of their geographical origin.